Navajo ABC : a Diné alphabet book - Tapahonso, Luci, 1953-; Tapahonso, Luci, 1953- (New York : Simon & Schuster Books for Young Readers, 1995)
ABC picture book introduces readers to the alphabet, while teaching about words and items important to the Navajo people.
Wilson's Children
Elem. School Library Collection
School Library Journal
1.5
K-3
Keywords: Navajo Indians -- Juvenile literature; Navajo language -- Glossaries, vocabularies, etc. -- Juvenile literature; Navajo Indians; Alphabet; Navajo language -- Glossaries, vocabularies, etc; Navajo Indians; Alphabet; Navajo language